The Representation of Women's Beauty and Sexuality in Sinhalese Theatre - Kankanamge, Sunethra (My University, 2017)
Attached

Woman has been a subject of discussion, viewed from a number of perspectives as beauty, love and sexuality from ancient times to the present as can be traced in a vast volume of literature in the world. According to the theories of Sanskrit literature as reflected in the works of poets and dramatists like Kalidasa, Sri Harshadeva, Bhasa 'Woman' is something very compulsory for them as a subject for ornation. Such ornation should focus on the woman from heir to feet with an ornated language'. According to the cross-cultural communication between India and Sri Lanka, many Sinhalese theatre directors have taken 'woman and the sexuality' as a tool for the performances from the beginning to the present time. They have focused on how the woman's beauty and gracefulness are important for the play. These attributes of women are integral to the development of the performance text on the stage. Sometimes they constitute the most important icon for the production. Many of the theatre productions have such a view in their representation of women's body. For example, in Ediriweera Sarachchandra's play 'Maname', the whole plot centers round the desire of the young princess Maname to be in the comfort of security and the personality of a man. The Director has chosen a girl for princess Maname who is very young and beautiful, with a typical woman's body as described by many poets in literature. She was an incarnation of beauty and sexuality as in the descriptions of many dramatists and poets. According to my view this is a tool which connects women's beauty and the sexuality with society. A similar representation of the woman's beauty and sexuality can be found in the plays such Sinhalese theatre directors as, Dharmasiri Bandaranayaka (Makarakshyana / The Dragon, 2011), Jayalath Manoratna (Horu Samaga Heluwen (Nude with thieves) 2008 and Dayananda Gunawardane (Gajaman Puwatha / The Lady, Gajaman). The source for primary data was the actual performances of particular plays. The secondary sources included the literature relevant to these areas.
Keywords: Woman, Sexuality, Beauty, performances, Sinhalese theatre